(Shelf-life Prediction of Instant Coffee Using an Accelerated Storage Study with Arrhenius Kinetics Model) - Sudibyo, Agus; F. Hutajulu, Tiurlan; -, Setyadjit (Balai Besar Industri Agro, 2010)
Instant coffee is one of Indonesias processed food product, that can be easily undergo a reduction in quality caused by adsorb of moisture. Nowadays, consumers demand products with good appearance, texture, taste and flavor whilst keeping their nutritional value. In order to meet consumers expectations for high-quality products, food industries must be conducted shelf-life studies that many times include the assessment of several analytical and sensory properties. Shelf-life dating using arrhenius method is one of an accelerated shelf-life test. The purpose of this study were to observe initial instant coffee characteristics, to observe the changes of quality during storage, to determine the quality critical point parameter for the product and the prediction of shelf-life of the product using arrhenius kineticsÂ method based on its quality control parameters. In the present study it was found that during storage of the product, moisture content and brightness level color value of the product aroma have decreased; and sensory evaluation based on volatile reducing substance (VRS) value and boiled coffee aroma. Critical parameter for this study is moisture content with the value of critical point for moisture content is 17.98%. Calculation based on Arrhenius kinetics equation at 30oC, RH 70% revealed a present of shelf-life for 588 days, at 45oC & RH 70% revealed a present of shelf-life for 398 days, and at 50oC & RH 70% revealed to make present of shelf-life for 352 days.